2017
DOI: 10.1021/acssuschemeng.7b03882
|View full text |Cite
|
Sign up to set email alerts
|

Mo2C-Based Electrocatalyst with Biomass-Derived Sulfur and Nitrogen Co-Doped Carbon as a Matrix for Hydrogen Evolution and Organic Pollutant Removal

Abstract: A Mo2C based electrocatalyst (Mo2C@SNC) was successfully synthesized with sulfur and nitrogen codoped carbon (SNC) as the matrix, which was derived from the shells of sunflower seeds. In the Mo2C/SNC, Mo2C particles that range in size from approximately 5 to 8 nm are evenly distributed in the sulfur and nitrogen codoped carbon matrix. Moreover, Mo2C/SNC has a large specific surface area with a mesoporous character. These particular structural features result in Mo2C@SNC having good electrocatalytic activity fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 65 publications
(81 reference statements)
0
57
0
Order By: Relevance
“…Chen et al [110] prepared MoSoy (Mo 2 C-Mo 2 Nh ybrid) from soybeans and ammonium molybdate ((NH 4 ) 6 Mo 7 O 24 ·4 H 2 O) via the solid state reaction ( Figure 12). [112] prepared Mo 2 Cb ased on sulphur and nitrogen co-doped carbon (SNC) derived from the shellso fs unflowers eeds. Furthermore, the MoSoyc omposites were supported on reduced graphene oxide (RGO) sheets for further enhancement of electrocatalytic activityf or HER.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Chen et al [110] prepared MoSoy (Mo 2 C-Mo 2 Nh ybrid) from soybeans and ammonium molybdate ((NH 4 ) 6 Mo 7 O 24 ·4 H 2 O) via the solid state reaction ( Figure 12). [112] prepared Mo 2 Cb ased on sulphur and nitrogen co-doped carbon (SNC) derived from the shellso fs unflowers eeds. Furthermore, the MoSoyc omposites were supported on reduced graphene oxide (RGO) sheets for further enhancement of electrocatalytic activityf or HER.…”
Section: Reviewmentioning
confidence: 99%
“…Due to the favourable cost of the biomass precursor and facile preparation method, the newly developed methodi si nexpensive, easy to scale up and environmentally friendly.A ne tal. [112] prepared Mo 2 Cb ased on sulphur and nitrogen co-doped carbon (SNC) derived from the shellso fs unflowers eeds. Cui et al [113] reported the synthesis of Mo 2 Cn anoparticles embedded in graphitic carbon sheets (Mo 2 C/GCSs) via ab iopolymer-induced solid-state reaction between (NH 4 ) 6 Mo 7 O 24 ·4 H 2 Oa nd sodium alginate( ALG).…”
Section: Molybdenum Carbidementioning
confidence: 99%
See 1 more Smart Citation
“…This method was utilized for the scalable fabrication of various TMC nano‐particle electrodes for electrochemical energy storage and conversion applications such as MIBs, SCs, RMABs, fuel cells and water splitting . Interestingly, among these rich carbon sources, biomasses (e.g., leaves, sodium alginate, glucose, fir sawdust, seeds, and legumes) were widely used as environmentally friendly and low cost carbon species to prepare TMCs . For instance, Chen et al .…”
Section: Controlled Synthesis and Its Structural Advantages In Energymentioning
confidence: 99%
“…[95] Interestingly,a mong these rich carbon sources, biomasses (e.g.,l eaves,s odium alginate, glucose, fir sawdust, seeds, and legumes) were widely used as environmentally friendly and low cost carbon species to prepare TMCs. [58,59,[96][97][98][99][100] For instance, Chen et al [59] reported the synthesis of molybdenumc arbide( MoSoy) nanoparticles by the solidstate reactiona th igh temperature. In this work, the authors used the biomass of the humble soybean, and earth-abundant metal of molybdenum (ammonium molybdate)t op reparem olybdenum carbide (Figure1a,b).…”
Section: Nanoparticlesmentioning
confidence: 99%